Factors predicting occult invasive carcinoma in women undergoing a "see and treat" approach - Chumnan Kietpeerakool (2018)
This study was undertaken to evaluate the incidence and independent predictors of unexpected invasive cancer of cervix in women with high-grade squamous intraepithelial lesions (HSIL) on Pap smear who had undergone "see and treat" approach. Women with HSIL on cervical cytology undergoing colposcopy, followed by loop electrosurgical excision procedure (LEEP) at Chiang Mai University Hospital between January 2001 and April 2006 were analyzed. During the study period, 446 women were identified. Mean age was 45.6 years (range, 25-78 years). One hundred and twenty-one (27.1%) women were postmenopausal. Unsatisfactory colposcopy was observed in 357 (80.0%) women. Of the 446 women, 76 (17.04%, 95% CI= 13.67 to 20.86) had invasive lesions on LEEP specimens. Multivariate analysis revealed that unsatisfactory colposcopy and premenopausal status were statistically significant independent predictors for invasive lesion on "see and treat" LEEP with an adjusted odds ratio of 4.68 (95%CI=1.82 to 12.03, P< 0.01) and 2.10 (95%CI=1.12 to 3.94, P=0.02), respectively. In conclusion, occult invasive lesion of the cervix was noted in 17% of women with HSIL Pap smear who underwent "see and treat" approach at our institute. Unsatisfactory colposcopy and premenopausal status were significant independent predictors of having such lesion.